Selection and adaptation to rapid changes in envitonmental pressures in humans - (:unkn) unknown (My University, 2018)
Throughout their recent evolutionary history, humans have colonized various ecological habitats, adopted different lifestyles and experienced massive demographic changes. However, the mechanisms of natural selection acting on the genome during periods of changes in selective constraints remain to be characterized. In this context, the study of exome sequences and genotyping data from 600 Pygmy rainforest hunter-gatherers and non-Pygmy farmers from 14 populations have allowed us to (1) evaluate the impact of their recent demographic changes on the efficacy of negative selection in their genomes and (2) identify the mechanisms of positive selection and the biological functions involved in the adaptation of Pygmies to their environments. Our results show that, despite their opposite recent demographic histories, Pygmy and non-Pygmy populations exhibit no differences in their additive and recessive mutational loads, and highlight the beneficial role of admixture on reducing the burden of recessive deleterious mutations. In addition, our results suggest that genes involved in both the regulation of immunity and metabolic pathways related to insulin are under convergent polygenic selection in several Pygmy populations from central Africa. To conclude, this works contributes to the better understanding of mechanisms of negative and positive natural selection in shaping the human genetic diversity.
Keywords: African Research